2009
DOI: 10.1038/hr.2009.136
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptor P2Y, G-protein coupled, 2 (P2RY2) gene is associated with cerebral infarction in Japanese subjects

Abstract: G-protein-coupled purinergic receptor P2Y2 (P2RY2) has an important role in the process of atherosclerosis related to cerebral infarction (CI). The aim of this study was to investigate the relationship between the P2RY2 gene and CI through a haplotypebased case-control study, including the separate analysis of two gender groups. A total of 237 CI patients and two control groups (control 1, 254; control 2, 255) were genotyped for five single nucleotide polymorphisms (SNPs) in the human P2RY2 gene (rs4944831, rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…[624] and Matejas et al [625] showed that EGR1, NR4A1, SIK1, CCN1, CEBPD (CCAAT enhancer binding protein delta), SOCS2, RGS2, KL (klotho), SOCS3, MMP1, CXCR4, CCN2, FST (follistatin), OGN (osteoglycin), CTLA4, KLF4, PTGER3, HBEGF (heparin binding EGF like growth factor), CCL2, OSM (oncostatin M), ERBB4, TNFSF11, MSTN (myostatin), ADAMTS1, CALCR (calcitonin receptor), INHBB (inhibin subunit beta B), EPO (erythropoietin), IL10, CEBPB (CCAAT enhancer binding protein beta), FOXO1, DKK1, GAS1, NPHP3, FGF2, ATF3, ANGPT2, SOCS1, IL1RAP, C9ORF72, BASP1, AKR1B10, SLC22A12, ACHE (acetylcholinesterase), TREM2, SCD (stearoyl-CoA desaturase), GCK (glucokinase), FOXP3, SLC22A2, EPHB2, LPL (lipoprotein lipase), ANGPTL8, HCN2, HSPA8, MB (myoglobin), KCNJ11, GLIS2, TNFSF13, LSS (lanosterol synthase), GAS6, AGRN (agrin), ACE2, NLRP6, DPEP1, TIMP3, CHI3L1, RASAL1, FAT1, GPBAR1, TREH (trehalase), CFB (complement factor B), FNDC5, HLA-G, MMP9, C4A and LAMB2 were associated with kidney disease, but these genes might be novel targets for NAFLD. [657], SOCS3 [658], MMP1 [659], CXCR4 [660], RASD1 [661], SLC7A11 [662], OGN (osteoglycin) [341], KLF4 [663], IL1RL1 [664], CCL2 [665], EPO (erythropoietin) [666], IL10 [667], ESR2 [668], VIP (vasoactive intestinal peptide) [669], FOXC1 [670], FOXO1 [671], S100B [672], DKK1 [673], SOCS1 [674], C9ORF72 [675], CTCFL (CCCTC-binding factor like) [676], S1PR2 [677], ACHE (acetylcholinesterase) [678], TREM2 [679], EPHB2 [680], LPL (lipoprotein lipase) [681], P2RY2 [682], ACE2 [683], CHI3L1 [684], HLA-G [685] and MMP9 [686] are found in cerebrovascular diseases, but these genes might be novel targets for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…[624] and Matejas et al [625] showed that EGR1, NR4A1, SIK1, CCN1, CEBPD (CCAAT enhancer binding protein delta), SOCS2, RGS2, KL (klotho), SOCS3, MMP1, CXCR4, CCN2, FST (follistatin), OGN (osteoglycin), CTLA4, KLF4, PTGER3, HBEGF (heparin binding EGF like growth factor), CCL2, OSM (oncostatin M), ERBB4, TNFSF11, MSTN (myostatin), ADAMTS1, CALCR (calcitonin receptor), INHBB (inhibin subunit beta B), EPO (erythropoietin), IL10, CEBPB (CCAAT enhancer binding protein beta), FOXO1, DKK1, GAS1, NPHP3, FGF2, ATF3, ANGPT2, SOCS1, IL1RAP, C9ORF72, BASP1, AKR1B10, SLC22A12, ACHE (acetylcholinesterase), TREM2, SCD (stearoyl-CoA desaturase), GCK (glucokinase), FOXP3, SLC22A2, EPHB2, LPL (lipoprotein lipase), ANGPTL8, HCN2, HSPA8, MB (myoglobin), KCNJ11, GLIS2, TNFSF13, LSS (lanosterol synthase), GAS6, AGRN (agrin), ACE2, NLRP6, DPEP1, TIMP3, CHI3L1, RASAL1, FAT1, GPBAR1, TREH (trehalase), CFB (complement factor B), FNDC5, HLA-G, MMP9, C4A and LAMB2 were associated with kidney disease, but these genes might be novel targets for NAFLD. [657], SOCS3 [658], MMP1 [659], CXCR4 [660], RASD1 [661], SLC7A11 [662], OGN (osteoglycin) [341], KLF4 [663], IL1RL1 [664], CCL2 [665], EPO (erythropoietin) [666], IL10 [667], ESR2 [668], VIP (vasoactive intestinal peptide) [669], FOXC1 [670], FOXO1 [671], S100B [672], DKK1 [673], SOCS1 [674], C9ORF72 [675], CTCFL (CCCTC-binding factor like) [676], S1PR2 [677], ACHE (acetylcholinesterase) [678], TREM2 [679], EPHB2 [680], LPL (lipoprotein lipase) [681], P2RY2 [682], ACE2 [683], CHI3L1 [684], HLA-G [685] and MMP9 [686] are found in cerebrovascular diseases, but these genes might be novel targets for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Different coding and non-coding SNPs (mostly common type) in P2RY1 and P2RY12 were previously evaluated in various IS population, however, the reported results have been conflicting so far [ 16 , 17 , 18 , 19 ]. It is worth mentioning that the possible associations of P2RY12 genetic variants, in a “gain-of-function” haplotype H2 of P2Y12 , with thromboembolic events (myocardial infarction (MI), IS, or deep venous thromboembolism/pulmonary embolism (DVT/PE)), were not confirmed in a prospective analysis of 14,916 initially healthy American men [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies addressed the impact or association of rare damaging polymorphisms in P2RY genes and IS. On the other hand, different SNPs (mostly common type) in P2RY1 and P2RY12 were previously evaluated in various IS cohorts, however, the reported results have been conflicting so far [ 16 , 17 , 18 , 19 , 20 ]. Out of all P2RY receptors, the greatest focus has been put on P2RY12 , which is expressed in megakaryocyte/platelet lineage, and contributes to progression of thrombosis and hemostasis to cerebrovascular events [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…P2Y2R signaling contributes to chemotaxis of leukocytes to the site of tissue damage as well as differentiation and proliferation of cells important for wound healing. In a Japanese genomic analysis, a specific P2Y2 haplotype was associated with an increased risk of arteriosclerosis and cerebral infarction, especially in women (Wang et al, 2009). However, P2Y2R and P2Y6R both promote the phagocytic clearance of apoptotic cells or bacteria, thereby contributing to the termination of inflammation (Koizumi et al, 2007), but endothelial or epithelial expression of P2Y6R can also play a role in innate immune activation (Riegel et al, 2011).…”
Section: Nucleotides and The P2 Axismentioning
confidence: 96%